2017
DOI: 10.18632/oncotarget.18547
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CALR and PDIA3 is a potential prognostic biomarker for non-small cell lung cancer

Abstract: Proteomic-based approaches for biomarker discovery are promising strategies used in cancer research. In this study, we performed quantitative proteomic analysis on 16 paired samples of non-small cell lung cancer (NSCLC) and adjacent non-tumor lung tissues using label-free quantitative proteomics and liquid chromatography-tandem mass spectrometry/mass spectrometry (LC-MS/MS) to identify differentially expressed proteins. A total of 91 proteins were differentially expressed in NSCLC compared with adjacent non-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
(35 reference statements)
5
16
0
Order By: Relevance
“…A body of evidences showed that CALR is highly expressed in tumor cells and transported onto cell membrane to serve as a C1q receptor and prophagocytic signal for macrophage phagocytosis of cancer cells and dead cells (12,13). Because the exposed CALR can be released into extracellular milieu (14,15), the serum CALR is highly elevated in the tumor patients and positively correlated to the prognosis of tumor (16,17). Therefore, serum CALR is considered as a useful biomarker in cancer diagnosis and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…A body of evidences showed that CALR is highly expressed in tumor cells and transported onto cell membrane to serve as a C1q receptor and prophagocytic signal for macrophage phagocytosis of cancer cells and dead cells (12,13). Because the exposed CALR can be released into extracellular milieu (14,15), the serum CALR is highly elevated in the tumor patients and positively correlated to the prognosis of tumor (16,17). Therefore, serum CALR is considered as a useful biomarker in cancer diagnosis and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty paired samples were excluded from analysis owing to incomplete patient information and/or sample absence. Therefore, IHC was performed as reported previously [4] on 70 matched specimens. Paraffin sections were dewaxed, followed by antigen retrieval with Tris-EDTA buffer (pH 9).…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin was used to counterstain the nuclei. Intensity and density of TOP2A-positive cells was evaluated and scored as reported before [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for canine mammary cancer, immunostaining for Derlin-1 showed that metastatic cells, the later stage of tumor progression, presented an increased stress-associated unfolded protein response (KLOPFLEISCH et al, 2010a) compared to non-metastatic samples.PDIA3 interacts with lectin chaperones calreticulin and calnexin to modulate folding of newly synthesized glycoproteinsBAIG;WILLIAMS, 2006). The low expression of PDIA3 have been associated to a poor overall survival for non-small lung cancer and gastric cancer, due to the formation of a complex with MHC class I and the high correlation with the expression of calreticulin, responsible for maintaining adequate calcium levels in organisms and also acting in ERBAIG;WILLIAMS, 2006;WANG et al, 2017b;SHIMODA et al, 2019). Calnexin is a highly abundant transmembrane chaperone which folds synthesized glycoproteins in the lumen of the endoplasmic reticulum(AEBI et al, 2010;SHIBATA et al, 2010), while the heat shock protein 5 (also known as BIP) is a master regulator of the UPR (MALHOTRA;KAUFMAN, 2007).…”
mentioning
confidence: 99%